Regulatory complexity and the quest for robust regulation - Prasanna Gai; Malcolm H. D. Kemp; Antonio Sánchez Serrano; Isabel Schnabel (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
This report argues that, in addition, financial regulation should be robust in the sense of being able to preserve its effectiveness when confronted with hard-to-predict developments and innovations. System robustness refers to the capacity of a system to maintain its core functions in the face of unexpected perturbations or disturbances. Regulatory robustness entails being able to cope with a variety of failure-inducing circumstances and behaviours, while not trying to offer the best-tailored response to each specific phenomenon. It therefore accounts for the interaction between Knightian uncertainty (the situation in which future contingencies or their probabilities are difficult or impossible to determine) and systemic risk. Arguably, the quest for robustness could improve the cost-effectiveness of the regulatory outcome while reducing its complexity.
Keywords: 330